Internalization Moral Values in Children in TPA and Its Implications for Character Building - Nanik, Nanik (DAWUH : Islamic Communication Journal, 2022)
The aims of this study were to: (1) To determine the concept of internalizing moral values in children at Al-Bayyinah TPA. (2). To find out the process of internalizing moral values in children at Al-Bayyinah TPA. (3). To find out the implications of the process of internalizing moral values in children at Al-Bayyinah TPA on character building. This study uses a qualitative descriptive method with a single research strategy fixed. Sources of data used are informants, places and events, as well as archives and documents. The sampling technique used is purposive sampling. Data collection techniques used are interviews, observation, and document analysis. In this study, validity was obtained by data triangulation techniques and method triangulation, as well as data analysis using interactive analysis, namely (1) data collection, (2) data reduction, (3) data presentation and (4) conclusion drawing. The results of this study can be concluded: (1) The concept of internalizing moral values in children at Al-Bayyinah TPA is with the Vision "Care for the Qur'anic Generation" & described in the TPA Mission, then the stages of implementation are carried out through the curriculum of learning activities teaching, Work Program, Discipline of students. (2) The process of internalizing moral values in children at the Al-Bayyinah TPA is in accordance with the initial concept as in the existing curriculum material, namely memorizing short letters in the Qur'an, Fiqh & Worship, Aqidah, Morals, History of the Prophet, Reading and Writing Quran. Various methods such as lectures, storytelling, group work, crafts, games/games. Supporting activities in the work program are student guardian meetings, friendship, rihlah, TPA competitions. (3) The implications for character building can be seen from whether there is awareness in children to behave well or badly, as well as changes in behavior caused by habits acquired by children during the learning process at the TPA.